CMR fast-SENC segmental intramyocardial LV strain monitors decline in heart function before ejection fraction in patient with arterial hypertension. (25th November 2020) - Montenbruck, M; Kelle, S; Esch, S; Schwarz, A.K; Giusca, S; Korosoglou, G; Steen, H
Abstract: Background: Left ventricular ejection fraction (LVEF) is commonly used to assess cardiac function for patients with chronic cardiac diseases. LVEF, like most systemic function assessments, detects dysfunction once enough damage has occurred to prevent common compensatory mechanisms from maintaining cardiac output. More sensitive metrics are being evaluated to more accurately identify subclinical regional dysfunction before cardiac remodeling results in changes in LVEF and global longitudinal strain (GLS). Fast-SENC intramyocardial strain (fSENC) is a unique cardiac magnetic resonance imaging (CMR) modality that measures intramyocardial contraction in 1 heartbeat per image plane. This prospective registry compares segmental fSENC to standard CMR calculations (e.g. LVEF, volumes, mass, etc.) for patients with arterial hypertension in the absence of non-ischemic cardiomyopathy. Methods: A single center, prospective registry of CMR scans acquired with a 1.5T scanner were evaluated for standard CMR calculations as well as fSENC scans. Intramyocardial LV & RV strain was quantified with MyoStrain software. Three short axis scans (basal, midventricular, & apical) were used to calculate peak strain in 16 LV & 6 RV longitudinal segments while three long axis scans (2-, 3-, & 4-chamber) were used to calculate 21 LV & 5 RV circumferential segments. Results: A total of 773 scans in 650 patients with arterial hypertension but without non-ischemic cardiomyopathies were included in the study. Patients had an average (± stdev) age of 64 (13) yrs and BMI of 28 (5) kg/m 2 ; 24% diabetes mellitus, 10% atrial fibrillation, 15% pulmonary disease, and 39% coronary artery disease. Figure 1 shows a Box & Whisker's plot demonstrating the non-linear relationship between segmental fSENC strain (% of normal LV segments ≤−17%) versus LVEF. The progression of hypertensive heart disease was associated with reduction in septal circumferential contraction despite normal LVEF. Conclusion: Segmental fSENC detects subclinical LV dysfunction in patients with early hypertensive heart disease before changes in LVEF. Evaluating segmental longitudinal and circumferential fSENC peak strain provides an alternative metric that shows consistent changes in cardiac function in patients with arterial hypertension. Funding Acknowledgement: Type of funding source: None